Palliative radiotherapy for symptomatic locally advanced breast cancer - Hoeltgen, Line; Meixner, Eva; Hoegen-Saßmannshausen, Philipp; Sandrini, Elisabetta; Weykamp, Fabian; Forster, Tobias; Vinsensia, Maria; Uzun-Lang, Kristin; König, Laila; Arians, Nathalie; Fremd, Carlo; Michel, Laura L.; et al. (Technology in cancer research & treatment, 2023)
Objective: Women with locally advanced breast cancer (LABC) or inoperable local recurrence often suffer from a significantly reduced quality of life (QOL) due to local tumor-associated pain, bleeding, exulceration, or malodorous discharge. We aimed to further investigate the benefit of radiotherapy (RT) for symptom relief while weighing the side-effects. Materials and methods: Patients who received symptom-oriented RT for palliative therapy of their LABC or local recurrence in the Department of Radiation Oncology at Heidelberg University Hospital between 2012 and 2021 were recorded. Clinical, pathological, and therapeutic data were collected and the oncological and symptomatic responses as well as therapy-associated toxicities were analyzed. Results: We retrospectively identified 26 consecutive women who received palliative RT with a median total dose of 39 Gy or single dose of 3 Gy in 13 fractions due to (impending) exulceration, pain, local hemorrhage, and/or vascular or plexus compression. With a median follow-up of 6.5 months after initiation of RT, overall survival at 6 and 12 months was 60.0% and 31.7%, and local control was 75.0% and 47.6%, respectively. Radiation had to be discontinued in 4 patients due to oncological clinical deterioration or death. When completed as initially planned, symptom improvement was achieved in 95% and WHO level reduction of analgesics in 28.6% of patients. In 36% (16%) of patients, local RT had already been indicated >3 months (>6 months) before the actual start of RT, but was delayed or not initiated among others in favor of drug alternatives or systemic therapies. RT-associated toxicities included only low-grade side-effects (CTCAE I degrees -II degrees) with predominantly skin erythema and fatigue even in the context of re-RT. Conclusion: Palliative RT in symptomatic LABC or locoregional recurrence is an effective treatment option for controlling local symptoms with only mild toxicity. It may thus improve QOL and should be considered early in palliative patient care management.
Zuerst online veröffentlicht: 10. April 2023
Gesehen am 09.11.2023